Measuring. Monitoring. Management. Control - V.S. Volkov; S.N. Bazykin; V.A. Bardin; K.S. Samohina; N.V. Volkova (Измерение, мониторинг, управление, контроль)
Background. The paper investigates the sensing element of a capacitive pressure sensor based on a silicon corrugated membrane. Materials and methods. Using finite element modeling, the parameters of the corrugation were determined, which make it possible to double the sensitivity compared to a flat membrane having similar overall dimensions. Results and conclusions. It is shown that the presence of an edge corrugation with a rectangular profile makes it possible to increase the sensitivity of the membrane.